Relationship between hockey skating speed and selected performance measures - Behm, D. G.; Wahl, M. J.; Button, D. C.; Power, K. E.; Anderson, K. G. (The Journal of Strength and Conditioning Research, 2005)
The objective of this study was to determine the relationship between specific performance measures and hockey skating speed. Thirty competitive secondary school and junior hockey players were timed for skating speed. Off-ice measures included a 40-yd (36.9-m) sprint, concentric squat jump, drop jump, 1 repetition maximum leg press, flexibility, and balance ratio (wobble board test). Pearson product moment correlations were used to quantify the relationships between the variables. Electromyographic (EMG) activity of the dominant vastus lateralis and biceps femoris was monitored in 12 of the players while skating, stopping, turning, and performing a change-of-direction drill. Significant correlations (p < 0.005) were found between skating performance and the sprint and balance tests. Further analysis demonstrated significant correlations between balance and players under the age of 19 years (r = -0.65) but not those over 19 years old (r = -0.28). The significant correlations with balance suggested that stability may be associated with skating speed in younger players. The low correlations with drop jumps suggested that short contact time stretch-shortening activities (i.e., low amplitude plyometrics) may not be an important factor. Electromyographic activities illustrated the very high activation levels associated with maximum skating speed.